Infectious Disease Management and Control with Povidone Iodine - Maren Eggers (Infectious Diseases and Therapy, 2019)
Abstract With reports of vancomycin-resistant enterococci recently emerging in hospital settings, renewed focus is turning to the importance of multifaceted infection prevention efforts. Careful compliance with established hygiene practices by healthcare workers together with effective antiseptic options is essential for the protection of patients from infectious agents. For over 60 years, povidone iodine (PVP-I) formulations have been shown to limit the impact and spread of infectious diseases with potent antiviral, antibacterial and antifungal effects. In addition to a lack of reported resistance, the benefits of PVP-I include an excellent safety profile and a broad spectrum of effect due to its multimodal action. Studies have shown that hand washing with PVP-I-based antiseptics is effective for the decontamination of skin, while PVP-I mouthwashes and gargles significantly reduce viral load in the oral cavity and the oropharynx. The importance of PVP-I has been emphasised by its inclusion in the World Health Organization’s list of essential medicines, and high potency for virucidal activity has been observed against viruses of significant global concern, including hepatitis A and influenza, as well as the Middle-East Respiratory Syndrome and Sudden Acute Respiratory Syndrome coronaviruses. Together with its diverse applications in antimicrobial control, broad accessibility across the globe, and outstanding safety and tolerability profile, PVP-I offers an affordable, potent, and widely available antiseptic option. Funding Mundipharma Singapore Holding Pte Limited.